FORMULATION OF LUBRICATING GREASE FOR AGRICULTURAL EQUIPMENT APPLICATION - Ratu Ulfi (Scientific Contributions Oil and Gas, 2016)
The formulation of environmentally friendly greases based on castor oil have been developed for agricultural equipment application. In order to improve base oil and tribological performances, several additives such as sterically hindered phenolic type antioxidants (AO), liquid mixture of amine phosphate as an extreme pressure (EP) and disodium sebacate as a corrosion inhibitor (CI) additive were added. The objective of this study is to develop a lubricating grease formula for agricultural equipment applications having high oxidation stability, good wear and corrosion protection, and excellence in terms of water resistance. The results of physical-chemical and performance examination show that the product developed has the following speci􀂿 cations: NLGI grade is 2, dropping point is at temperature of 192.5oC, unworked and worked penetrations are 255 mm/10 and 307 mm/10 respectively. The copper strip corrosion is 1a, and scar diameter is 0.57 mm. The physical-chemical characterics of the grease developed still meet speci􀂿 cations, especially for agricultural equipment application.